Breastfeeding and the nutritional transition in the Latin American and Caribbean Region: a success story? - Pérez-Escamilla Rafael (Cadernos de Saúde Pública, 2003)
The objectives of this paper are to examine recent breastfeeding duration trends in Latin America and the Caribbean to document: (a) rural-urban differentials, (b) differences in educational levels, and (c) changes in breastfeeding duration across time. Secondary data analyses were conducted with 23 Demographic and Health Surveys collected between the mid-1980s and mid-1990s. Results indicate that median breastfeeding duration is still greater in rural (as compared to urban) areas and among less (versus more) educated women, although these differentials are decreasing with time. In five of the six countries examined for secular trends, breastfeeding duration continues to increase in both rural and urban areas. Breastfeeding duration in urban and rural areas was strongly correlated within countries. Breastfeeding duration improved more among women with the highest and declined among those with the lowest levels of education. Results indicate that breastfeeding duration has increased in Latin America and the Caribbean at a time when the opposite was predicted, given the region's increased urbanization. Breastfeeding protection policies and promotion programs may explain part of the increase in breastfeeding duration.